A Dual‐Ligand Porous Coordination Polymer Chemiresistor with Modulated Conductivity and Porosity - Yao, Ming‐Shui; Zheng, Jia‐Jia; Wu, Ai‐Qian; Xu, Gang; Nagarkar, Sanjog S.; Zhang, Gen; Tsujimoto, Masahiko; Sakaki, Shigeyoshi; Horike, Satoshi; Otake, Kenichi; Kitagawa, Susumu (Angewandte Chemie International Edition, 2020)
Single‐ligand‐based electronically conductive porous coordination polymers/metal–organic frameworks (EC‐PCPs/MOFs) fail to meet the requirements of numerous electronic applications owing to their limited tunability in terms of both conductivity and topology. In this study, a new 2D π‐conjugated EC‐MOF containing copper units with mixed trigonal ligands was developed: Cu3(HHTP)(THQ) (HHTP=2,3,6,7,10,11‐hexahydrotriphenylene, THQ=tetrahydroxy‐1,4‐quinone). The modulated conductivity (σ≈2.53×10−5 S cm−1 with an activation energy of 0.30 eV) and high porosity (ca. 441.2 m2 g−1) of the Cu3(HHTP)(THQ) semiconductive nanowires provided an appropriate resistance baseline and highly accessible areas for the development of an excellent chemiresistive gas sensor. Makes sense: As two ligands offer more opportunity than one to tune MOF conductivity and topology, a 2D π‐conjugated copper‐based electronically conductive MOF with two different trigonal organic ligands was developed (see structure). The semiconductivity and high porosity of the resulting nanowires provided a low conductivity baseline and highly accessible surface areas, thus resulting in excellent room‐temperature chemiresistive sensing properties.